The Role of the Village Consultative Body in Temdak Village, Seberang Musi District, Kepahiang Regency - Tri Purwanti (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2021)
Since the stipulation of Permendagri of the Republic of Indonesia Number 110 of 2016 concerning the Village Consultative Body (BPD), in Kepahiang Regency all villages have had BPD. However, from a number of Village Consultative Body, when viewed from the activity of BPD from the number of village regulation products that have been made, not all of them carry out activities as they should, namely the Perdes products produced at least include the Perdes on organizational structure and village governance work, village head income. and village officials, village fees, nomination procedures, appointment and temporary dismissal and dismissal of village officials, village institutions, as well as village revenue and expenditure budgets. The purpose of this study is to describe the implementation of the role of the Village Consultative Body in Temdak Village, Seberang Musi District, Kepahiang Regency. In this study a descriptive qualitative method was used to analyze the existing problems, with the findings in the field that the implementation of the role of legislation has been running but is still not optimal because not all members are technically active and only four members are actually actively involved technically in the drafting process. The implementation of supervision carried out by the BPD in general is strict, namely by paying attention to what is stated in the village regulation, then comparing it with what is actually being done by the village government, and if there is a discrepancy, the BPD will ask for an explanation from the village government. In the nurturing role, namely by maintaining and introducing existing customs and arts through the commemoration of national holidays and religious holidays at the village, sub-district and district levels..